ROMANTISISME DALAM NOVEL PETER PAN KARYA J. M. BARRIE - RAMBING, XINETH ABYGAILL MIZABIA; SIGARLAKI, STEPHANI J.; WAROUW, MAYA P. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis skripsi entitled â€œRomantisisme dalam Novel Peter Pan karya J. M. Barrieâ€, is focused on Romanticism which is a comprehension or way of rational thinking of a civilization that put forward feeling, emotion, desire, and will. All of those are associated with beauty. The aim of this research is to identify, analyze, and explain the aspects of Romanticism within the novel. In order to achieve those aims, philosophy of romanticism and the literary criticism are coined by Lovejoy and Wellek-Warren. This research used descriptive method and two approaches namely intrinsic and extrinsic approaches. The intrinsic approach is used for analyzing and interpreting the work on romanticism through the plot, character, and setting which are portrayed in Peter Pan. The extrinsic approach is used to analyze the romanticism in Peter Pan and interpret the meaning of its aspects based on the authorâ€™s perspective. Moreover, the result of the research shows that the philosophy of romanticism is also included by J. M. Barrie in Peter Pan. The aspects of romanticism found in the novel are Optimist, Paradox, Selfless, Imagination, and Happiness.Keywords: romanticism, philosophy, novel, Peter Pan